Taste Perception from Jamu Drinks Color for Younger Generation by using Photo Products - Andreas Kurniawan; Yasraf Amir Piliang; Agung Eko Budiwaspada (Research Synergy Foundation, 2023)
Jamu is a traditional herbal drink from Indonesia that has been inherited from generation to generation. Jamu drinks have a variety of recipes since their ingredients are derived from a combination of typical Indonesian spices that can be obtained in local markets. Previously, jamu was frequently associated with a bitter taste, but due to improvements and innovations, it may now adapt to the preferences of the younger generation. Moreover, modification of a recipe's look involving different hues may cause consumers to speculate about its taste. This study examines taste perception from the Indonesian traditional herbal drinks